The Effect of Houseplant Ratio in Residential Interior on Human Positive Emotions - Sabiela, Yaritsa Husni; Wibisono, Andriyanto (Jurnal Desain Interior, 2024)
Urban populations worldwide have reached half of the global population. The increasing dominance of urban human civilization is closely tied to the changing lifestyles of individuals. Present generations spend 90 percent of their time indoors, impacting the intensity of human interaction with the external environment. These lifestyle changes have engendered negative emotional effects on inhabitants, thereby driving the trend of incorporating plants into interior spaces to evoke positive emotions, particularly within residential settings. This research aims to ascertain: 1) the optimal ratio of plants used in residential interiors to evoke the best positive emotional effects for users, and 2) how the selection of plants in residential interiors influences users' positive emotions. A qualitative approach was employed in this study, utilizing questionnaire surveys and interviews to gather preferences, which were subsequently utilized in simulated room experiments. The research findings revealed that the smallest ratio of plants in simulated rooms, considering the proportion of space and volume among rooms, furniture, and human circulation, yielded the most significant positive emotional effects. These findings contribute to understanding the proportion of plant additions in residential interiors to maximize positive emotional effects for the 17-35 age group.